Identification of Fasciola species based on mitochondrial and nuclear DNA reveals the co-existence of intermediate Fasciola and Fasciola gigantica in Thailand - Wannasan,A. (Academic Press Inc., 2015)
© 2014 Elsevier Inc.. Molecular techniques were used to identify Fasciola species collected from Chiang Mai Thailand. Morphometrically, 65 stained and 45 fresh worms collected from cattle suggested the possible occurrence of both F. gigantica and F. hepatica. Twenty-two worms comprising 15 from cattle and 7 from human patients, were identified subsequently based on three genetic markers: mitochondrial nicotinamide adenine dinucleotide dehydrogenase subunit 1 (. nad1), mitochondrial cytochrome c oxidase subunit 1 (. cox1) and nuclear ribosomal internal transcribed spacer 2 (ITS2). All of them presented the F. gigantica type in maternally inherited mitochondrial sequences (. nad1 and cox1), with six types in each sequence (FgNDI-CM1 to FgNDI-CM6 and FgCOI-CM1 to FgCOI-CM6, respectively). Remarkably, the predominant nad1 type, FgNDI-CM6, was identical to that of aspermic Fasciola sp. formerly reported from Thailand, Japan, Korea, China, Vietnam, and Myanmar. ITS2 sequences were analyzed successfully in 20 worms. Fifteen worms showed the F. gigantica type and five (including one worm from a patient) had mixed ITS2 sequences of both F. gigantica and F. hepatica in the same worms, with additional heterogeneity within both ITS2 types. This study revealed the intermediate form of Fasciola coexisting with F. gigantica for the first time in Thailand.